Pengaruh Sarana Prasarana dan Sumber Daya Manusia terhadap Kualitas Layanan Pendidikan di Sekolah Islam Al Azhar Bukittinggi - Rhafiiqul Azhari Karim; Afrinaldi; Nunu Burhanuddin; Hamdi Abdul Karim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of infrastructure and human resources on the quality of educational services at Al Azhar Islamic School Bukittinggi. The research uses a quantitative approach with a survey method on elementary and junior high school students. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results of the study show that infrastructure and human resources have a significant effect on the quality of education services, both partially and simultaneously. The results of the simultaneous test showed a significance value of 0.000 < 0.05. The determination coefficient showed that the two variables contributed 22.9% at the elementary level and 73.9% at the junior high school level. These findings show that improving the quality of education services can be done through optimizing infrastructure facilities and developing human resources in a sustainable manner.